The Impact of Coaching on The Resilience of The Agribusiness MSMEs - Yurnita, Amelia; Maryadi, Maryadi; Sari, Dwi Wulan (Forum Kerjasama Pendidikan Tinggi, 2025)
The Ministry of State-Owned Enterprises, in collaboration with state-owned firms, established the Rumah BUMN as a communal space to convene, educate, and support MSME stakeholders in becoming high-quality Indonesian MSMEs. Rumah BUMN Sumsel (RBS) affiliated with Company Social Responsibility Department of PT. Pusri Palembang, is dedicated to supporting MSME partners through three primary initiatives: competency enhancement, market access, and capital accessibility. This study will delineate the attributes of MSMEs supported by the South Sumatra Rumah BUMN and assess the coaching program implemented RBS regarding the sustainability of agribusiness MSMEs through SEM-PLS (Structural Equation Modelling-Partial Least Square) correlation analysis. The metrics employed to assess business sustainability variables include augmented MSME revenue, business expansion, product quality, competitiveness, and operational efficiency. Data analysis results from 100 respondents using the SmartPLS3 program indicate that, for MSMEs in the agricultural sector, the variables significantly influencing business sustainability are marketing access (p-value = 0.013) and capital availability (p-value = 0.000). The variable of competency enhancement, with a p-value of 0.302, indicates an insignificant result in the agriculture MSME sector. Business sustainability is significantly reliant on money and extensive market reach. Despite an improvement in competence, the absence of adequate money and a market capable of absorbing products may jeopardise corporate continuation.